Yokohama Chess Club - Chess Club Yokohama (s.n., 1890)
Officers 1890. |Rules of the Yokohama Chess Club 1890. |Annual Report 1891-1892 [na doklejonym wycinku z gazety]
st. zas. Os.
Keywords: szachy; Kluby i związki szachowe; Yokohama